Breastfeeding mobile applications assistance in Brazil: a scoping review protocol - Iga Carnevalli Leal; Ester Florens Guerra Gouvêa; Larissa Melgaço Campos; Ana Júlia Delfim de Oliveira; Daiana Carola de Souza Teles; Teresa Raquel Morais Silva; Joyce Marques Barroso; Andréa Rodrigues Motta; Renata Maria Moreira Moraes Furlan (Revista CEFAC, 2023)
ABSTRACT Purpose: to present a scoping review protocol to identify and analyze free applications available for Android and iOS operating systems to assist nursing mothers in terms of breastfeeding. Methods: the methodological structure of this scoping review has nine stages: developing the research question; defining descriptors; establishing application inclusion and exclusion criteria; locating applications; listing applications; selecting them by title and icon analysis; collecting application data; selecting them by application data analysis and quality assessment. The research question was developed based on the participants-concept-context strategy. Breastfeeding mobile applications assistance will be searched in Google Play and Apple Store. Two independent raters will select applications, collect data, and assess their quality. Quality assessment will use the Mobile App Rating Scale, which will be correlated with user ratings. Final Considerations: this research presented a nine-stage scoping review protocol aimed at identifying and analyzing free applications available for Android and iOS operating systems to help nursing mothers in terms of breastfeeding. The protocol is ready to be implemented.